PERLINDUNGAN KONSUMEN TERHADAP PENYANDANG TUNA NETRA SEBAGAI PENGGUNA JASA PERBANKAN DI KOTA PEKANBARU (STUDI DI BANK RAKYAT INDONESIA UNIT BUKIT BARISAN) - Sri Yani Yolanda; Firdaus Firdaus; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Business actors in public services in the field of banking services, theBank Rakyat Indonesia (BRI) Unit Bukit Barisan Kota Pekanbaru in its servicehas the responsibility for the obligation to guarantee the rights of consumers orcustomers who use the BRI Bukit Barisan Unit in Pekanbaru. Bearing in mindthat Persons with Blindness are consumers who are vulnerable groups of people,then protection should be given more with regard to its specificity, namely in LawNumber 8 of 2016 concerning Persons with Disabilities. In its implementation, theBRI Bukit Barisan Unit in the City of Pekanbaru should carry out its obligationsin fulfilling consumer rights as stated in Law Number 8 of 1999 concerningConsumer Protection. But in reality there have been social inequalities betweenthe BRI Bukit Barisan Unit in the City of Pekanbaru and customers withDisabilities. BRI's Bukit Barisan Unit in Pekanbaru City does not provide specialfacilities and conveniences for the Blind Person as regulated. The problems andobjectives that will be discussed in this paper are to find out how consumerprotection against the person with blindness as a user of banking services in thecity of Pekanbaru (Study at the Bukit Barisan Unit of the People's BankIndonesia).This type of research is sociological. This research was conducted at theBRI Bukit Barisan Unit in Pekanbaru City, while the population and sampleswere all parties related to the problems examined in this study, data sources used,primary data, secondary data and tertiary data, data collection techniques in thisstudy with interviews, questionnaires and literature studies.The results of the study can be concluded that the BRI Bukit BarisanUnit in the City of Pekanbaru has not fully implemented the rights of blind clients.Special facilities intended for blind clients are not yet available at the BukitBarisan BRI Unit in Pekanbaru City. This causes blind clients to feel that theirrights as consumers are not fulfilled by the BRI Bukit Barisan Unit in PekanbaruCity. Suggestions for BRI Bukit Barisan Unit in Pekanbaru City to furtherimprove services for all customers, especially those with blindness.Keywords: Consumer Protection - Consumers - People with Blindness - BRIBukit Barisan Unit, Pekanbaru City